2021
DOI: 10.24940/ijird/2021/v10/i11/nov21014
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Use of Computers in Teaching and Learning in Public Secondary Schools in Arusha City Council, Tanzania

Abstract: This study investigated the extent to which teachers use computers in teaching and learning in public secondary schools in Arusha city council, Tanzania. Rogers' Diffusion of Innovation theory guided the study. Convergent parallel design under mixed research approach was adopted. Purposive and stratified simple random technique were used to obtain 110 respondents where by 100 were teachers and 10 were heads of schools. Instruments of data collection were questionnaires, structured Interview guide and observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, studies conducted by Mchalo et al (2021); Noyi (2013) and Mandari (2018) in various educational institutions in Tanzania found that computers, photocopy machines, scanners, printers and Internet facilities were readily available. These findings also align with the findings of Toyo (2017) and Okorieocha et al (2019) who designed studies to investigate ICT adoption on the educational growth of colleges in Nigeria and found that computers, photocopy machines, scanners, printers and Internet facilities were available.…”
Section: Demographic Information Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies conducted by Mchalo et al (2021); Noyi (2013) and Mandari (2018) in various educational institutions in Tanzania found that computers, photocopy machines, scanners, printers and Internet facilities were readily available. These findings also align with the findings of Toyo (2017) and Okorieocha et al (2019) who designed studies to investigate ICT adoption on the educational growth of colleges in Nigeria and found that computers, photocopy machines, scanners, printers and Internet facilities were available.…”
Section: Demographic Information Of Participantsmentioning
confidence: 99%
“…The low utilization of desktop computers in teaching and learning process may reflect a shift towards more portable and versatile devices (Chirwa, 2018b;Mchalo et al, 2021). However, observations made by the researcher revealed that desktop computers were fixed in instructor's offices.…”
Section: Research Questionmentioning
confidence: 99%